Analysis of a Two‐Stage Fuel Reactor System for the Chemical‐Looping Combustion of Lignite and Bituminous Coal. Issue 10 (4th July 2016) - Haus, Johannes; Lyu, Kai; Hartge, Ernst‐Ulrich; Heinrich, Stefan; Werther, Joachim
Abstract: To investigate the influence of the fuel characteristics on the conversion behavior in a chemical‐looping combustion facility, lignite coal dust ( d 90, 3 =233 μm) and two fractions of bituminous coal with different particle sizes (fine fraction d 90, 3 =163 μm, coarse fraction d 50, 3 =707 μm) were used as solid fuel. To improve the conversion performance, a pilot plant with a rated power of 25 kW was constructed with a two‐stage fuel reactor. The influence of the fuel composition, particle size, and the presence/absence of elemental oxygen on the conversion in the fuel reactor are presented. The used oxygen carrier was produced by the impregnation of γ‐alumina oxide with copper oxide, which is able to release gaseous oxygen, but loses this ability because of deactivation. The lignite dust shows a very good conversion performance and carbon capture efficiencies over 95 % as well as oxygen demands below 2 %. Both bituminous coal fractions have a good performance with regard to fuel conversion and oxygen demand but they suffer from a high carbon slip. Hence the carbon capture efficiency is around 60 % for the fine fraction and 40 % for the coarse one. The performance improvement as a result of the second stage was investigated separately, and we proved that it enhances the overall conversion. In addition, the oxygen carrier generated a favorable reaction environment by releasing elemental oxygen in the second stage of the fuel reactor. Abstract : At the coal face : The chemical‐looping combustion of solid fuels often suffers from high amounts of combustibles that leave the reactor unconverted. In this work, a two‐stage reactor to reduce this shortcoming is operated on bituminous coal and lignite. The oxygen demand was below 2 %, even at fairly low temperatures.